Hypertrophic cranial pachymeningitis: assessment with CT and MR imaging. - Martin, N; Masson, C; Henin, D; Mompoint, D; Marsault, C; Nahum, H (American Journal of Neuroradiology, 1989)
Three patients with diffuse idiopathic cranial pachymeningitis with predominant involvement of the tentorium and falx are reported. Progressively increasing headaches were the usual symptoms, along with ataxia and various cranial nerve palsies. CT in all cases and MR imaging in two cases detected isolated thickened dura mater. In one case, MR depicted dural involvement as a very large, hypointense area with fine hyperintense edges on T2-weighted images. Microscopic examination of thickened dura revealed extensive fibrotic tissue with a chronic inflammatory infiltrate containing lymphocytes, plasma cells, and scattered eosinophils; these findings closely paralleled the MR features. Only four cases with similar pathologies have been described, all before the advent of CT and MR. We discuss the different causes of thickened dura mater as well as the significance of the fact that dural thickening can be responsible for occlusion of the dural sinuses. Cranial pachymeningitis is a rarely reported disease that can resemble other disorders associated with tentorial thickening; CT and MR can help differentiate it from these other disorders.